Basic researchChanges of gastric intramucosal pH in obese patients undergoing laparoscopic and open cholecystectomy - Matsota, Paraskevi; Sidiropoulou, Tatiana; Pandazi, Ageliki; Batistaki, Chrysanthi; Matiatou, Stamo; Kostopanagiotou, Georgia (Archives of Medical Science, 2007)
Introduction: Gastric intramucosal pH (pHi) reflects splanchnic perfusion, while pneumoperitoneum may cause disturbances in splanchnic perfusion by increasing intra-abdominal pressure (IAP). Obesity is associated with increased IAP. The aim of this study was to compare the effects of laparoscopic cholecystectomy and open cholecystectomy on pHi in obese patients. Material and methods: Sixty obese patients (BMI 30-40 kg/m 2 ), aged 30-70 years, scheduled for cholecystectomy under standardized general anaesthesia were randomized to receive either laparoscopic cholecystectomy (LC group, n=30) or open cholecystectomy (OC group, n=30). pHi was calculated using gastric air tonometry. Measurements of pHi occurred in four phases: phase I (after induction of anaesthesia but before surgical incision), phase II (15 min of pneumoperitoneum in the LC group or 15 min after surgical incision in the OC group), phase III (end of operation) and phase IV (60 min after patients’ awakening). Results: Intraoperatively, a slight decrease of pHi was observed in both groups without reaching significance. In contrast, at the 1st postoperative hour a statistically significant difference was revealed between the two groups (OC: 7.41±0.038 vs. LC: 7.37±0.05, p<0.001), both due to the ongoing decrease of pHi in the LC group and the tendency of pHi in the OC group to increase. Despite this, pHi values were within normal ranges during our whole observation period. Conclusions: Laparoscopic cholecystectomy in obese patients compared to open cholecystectomy caused a significant decrease of pHi in the 1st postoperative hour, although pHi remained within normal values.